Negotiating Gender and Informality: Domestic Roles and Women’s Economic Participation in Margibi, Liberia - Johnson, Martha; Kollie, Samuel Tonny; Diallo, Aissatou; Bah, Mamadou (Baileo: Jurnal Sosial Humaniora, 2025)
This article explores how women in Margibi County, Liberia, negotiate domestic roles alongside participation in the informal economy. The study addresses tensions between patriarchal household structures and economic needs, focusing on how negotiation shapes women’s experiences, strategies, and agency. It aims to analyze women’s involvement in the informal sector, examine their strategies for balancing domestic and public roles, and explain the social implications of gender negotiations for families and communities. A qualitative approach informed by gender sociology was applied. Forty women engaged in informal work—including vendors, daily laborers, and service providers—were selected through purposive sampling. Data were collected through in-depth interviews, participant observation in markets and households, and document analysis from governmental and non-governmental sources. Findings reveal that women actively participate in informal economies as survival strategies but face constraints from the dual burden of domestic and public work. Gender negotiations manifest through compromise strategies, including income sharing with spouses, involving children in household tasks, and redistributing domestic labor within communities. Women’s economic contributions foster hidden forms of agency that influence household decision-making, despite persistent patriarchal discourse. Informality emerges not only as work outside the formal sector but also as a social arena where gender identities and power relations are reshaped. This study contributes novel insights by linking informality, domestic negotiation, and patriarchy in Liberia, advancing sociological understandings of women’s agency across both public and domestic spheres.